Thinking Europe A History of the European Idea since 1800 - Andrén, Mats (Making Sense of History, 2023)
Presenting a new historical narrative on European integration and identity this title examines how the concept of Europe has been entangled in a dynamic and dramatic tension between calls for unity and arguments for borders and division. Through an in-depth intellectual history of the idea of Europe, Mats Andren interrogates the concept of integration and more recent debates surrounding European identity across the nineteenth and early twentieth centuries and the post-war period. Applying a broad range of original sources this unique work will be key reading for students and researchers studying European History, European Studies, Political History and related fields.